Survival Analisis Jenis Pendidikan terhadap Durasi Menganggur di Sumatera Tahun 2020 - Wisdawati, Ramadhana Aulia; Ridwan, Endrizal; Primayesa, Elvina (Jurnal Informatika Ekonomi Bisnis, 2023)
The duration of unemployment is the time it takes for workers to search for and find a job that best matches their skills and preferences. This research aims to analyze the duration of unemployment in Sumatra. The analytical technique used in this study is survival analysis using Cox regression. The data used in this research are secondary data sourced from the National Labor Force Survey in August 2020. The total number of observation units used in this study is 5,936 individuals. The research findings show that, on average, the duration of long-term unemployment in Sumatra is 2.95 months. The test results indicate that education, experience, and regional classification variables have a significant effect on the duration of unemployment in Sumatra.